Polyethylene naphthalate composite material with high impact strength and preparation method thereof

Through the low crosslinked polyacrylate elastomer melt blended with PEN resin, the impact strength and processing performance of polyethylene naphthalate are significantly improved, and the problem of low impact strength of PEN resin is solved, achieving excellent maintenance Based on thermal stability, the effect of significantly improving impact toughness.

CN119192798AActive Publication Date: 2024-12-27XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411478263.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-27
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The impact strength of polyethylene naphthalate (PEN) resin is low, which limits its wide application in automotive parts, electronic and electrical shells and packaging materials. There are relatively few existing toughening studies, making it difficult to maintain the material. Other excellent performance.

Method used

Polyacrylate elastomer with low crosslinking structure is melt blended with PEN resin, and through polymerization and self-crosslinking reactions during the preparation process, a composite material with high impact strength is formed, including butyl acrylate and acrylate. Monomers such as ester and hydroxyethyl methacrylate are polymerized and self-crosslinking reaction is carried out under heating conditions. The obtained polyacrylate elastomer is mixed with PEN resin and then melt-extruded in a twin-screw extruder.

Benefits of technology

It significantly improves the impact toughness of composite materials and improves the impact strength by 40-62.5 times, while maintaining the high thermal stability and good processing performance of the materials. It is suitable for the production of products in high temperature environments and complex shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192798A_ABST
    Figure CN119192798A_ABST
Patent Text Reader

Abstract

The invention discloses a high-impact-strength polyethylene naphthalate composite material and a preparation method thereof, and belongs to the field of composites.The preparation method includes the steps that 100 parts by mass of polyethylene naphthalate, 10-40 parts by mass of polyacrylate elastomer, 0.5-1.5 parts by mass of heat stabilizer and 0.5-1 part by mass of antioxidant additive are mixed to be uniform, melt extrusion is conducted, and the high-impact-strength polyethylene naphthalate composite material is obtained. The polyethylene naphthalate composite material with high impact strength is obtained. According to the invention, the polyacrylate elastomer with low crosslinking density is dispersed into the PEN resin to form a phase morphology with the characteristic of low matrix ligament thickness, and the morphology can effectively increase the ductility of PEN, so that the PEN shows better energy absorption and deformability under impact, thereby avoiding brittle rupture. The polyethylene naphthalate composite material provided by the invention is excellent in comprehensive performance, simple in preparation process, easily available in raw materials and wide in industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation, and particularly relates to a polyethylene naphthalate composite material with high impact strength and a preparation method thereof. Background Art

[0002] Polyethylene naphthalate (PEN) resin is a high-performance polyester material made from the monomers 2,6-naphthalate and ethylene glycol through polycondensation. PEN resin has the characteristics of high modulus, high strength and heat resistance, and is one of the most ideal engineering plastics. Therefore, as one of the emerging chemical materials that the Ministry of Industry and Information Technology and other departments have clearly pointed out to be vigorously developed, PEN resin has made significant progress in research and development and application in recent years, and is widely used in infrastructure construction, smart construction, impact-resistant fabrics, national defense and military industry, smart cars, smart sensors and other fields. This material is regarded as one of the most promising polymer materials in the 21st century due to its excellent physical and chemical properties.

[0003] The reason why PEN resin exhibits excellent performance in many applications is mainly attributed to its naphthalene ring structure. The naphthalene ring is a highly rigid aromatic ring structure, and its presence makes the PEN molecular chain more rigid. Compared with polyethylene terephthalate (PET), this improvement in rigidity brings significant performance advantages in thermal properties, mechanical properties, solvent resistance, and radiation resistance to PEN. Although PEN has many excellent properties mentioned above, due to the high rigidity of the naphthalene ring in its molecular chain, it is difficult for PEN products to undergo plastic deformation and break after being subjected to force, and the macroscopic manifestation is low impact strength, which seriously restricts its industrial application. The high rigidity of the molecular chain means that it is difficult for the chain segments to rotate and deform freely under the action of external forces, resulting in greater brittleness of the material, especially poor impact resistance when subjected to impact. High modulus and low toughness are typical characteristics of PEN resin. Although its high modulus makes the material outstanding in rigidity, its low toughness limits its application in high impact load or deformation environments. The disadvantage of insufficient impact strength has particularly limited the widespread application of PEN in automotive parts, electronic and electrical housings, and certain packaging materials, which usually require the material to have a certain degree of flexibility to cope with complex environmental stresses and impact loads. Therefore, improving the toughness of PEN to achieve its wider application scenarios has become an important topic in the field of materials research.

[0004] The results show that melt blending with another elastomeric material is one of the most effective and common toughening methods to date. During the blending process, the elastomeric material can absorb and disperse stress by forming a dispersed phase, thereby effectively improving the toughness of the material. For example, significant progress has been made in the study of PET toughening, providing a good reference: Patent CN1279115C uses an elastomer containing epoxy groups as a toughening phase, which effectively improves the impact strength after melt blending with PET; CN102382432A melt blends a thermoplastic polyurethane elastomer with a PET resin to obtain a high-toughness PET composite material; CN105482387B blends PET with a thermoplastic elastomer to obtain a transparent PET sheet with high impact strength.

[0005] However, although the research in the field of PET toughening is relatively mature, the research on toughening of PEN resin is still in its early stages. Existing research work is more focused on the performance enhancement of PEN film materials, such as improving its barrier properties, thermal stability and UV resistance, but there are relatively few studies on improving the toughness of PEN. For example, the CN103396658A patent proposes a method of melt-blending an elastomer and glass fiber with a PEN resin at the same time to prepare a PEN composite material with high strength and high modulus. However, the composite material is still limited in improving the impact strength, showing that there is still great research potential and room for improvement in the direction of toughening.

[0006] With the increasing requirements for material performance in the automotive, electronic appliances, smart devices and other industries, especially the high requirements for toughness and impact resistance, designing suitable elastomers to toughen PEN resins has become a technical problem that needs to be solved urgently. The blending of elastomers and PEN resins should not only consider improving impact toughness, but also maintain or minimize the impact on other excellent properties of PEN, such as its high thermal stability, excellent chemical resistance and radiation resistance. Summary of the invention

[0007] In view of the problem of low impact strength of PEN resin in the prior art, the object of the present invention is to provide a high-impact-strength polyethylene naphthalate composite material and a preparation method thereof. The composite material prepared by the method has the properties of high strength, high modulus and high impact strength.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a polyethylene naphthalate composite material with high impact strength comprises the following steps: 100 parts of polyethylene naphthalate, 10-40 parts of polyacrylate elastomer, 0.5-1.5 parts of heat stabilizer and 0.5-1 parts of antioxidant are mixed uniformly by mass, melt-extruded and obtained to obtain polyethylene naphthalate composite material with high impact strength.

[0009] A further improvement of the present invention is that the polyacrylate elastomer is prepared by the following process: 30-50 parts by mass of butyl acrylate, 30-50 parts by mass of methyl methacrylate, 5-30 parts by mass of hydroxyethyl methacrylate, 1-30 parts by mass of glycidyl methacrylate, 0.5-1.5 parts by mass of an oil-soluble initiator and 200 parts by mass of a solvent are subjected to a polymerization reaction to obtain a polyacrylate solution; and the polyacrylate solution is subjected to a self-crosslinking reaction under heating to obtain a polyacrylate elastomer.

[0010] A further improvement of the present invention is that the oil-soluble initiator is one of azobisisobutyronitrile, benzoyl peroxide and di-tert-butyl peroxide.

[0011] A further improvement of the present invention is that the solvent is one or a mixture of two of toluene, xylene, mesitylene, ethyl acetate and butyl acetate.

[0012] A further improvement of the present invention is that the polymerization reaction temperature is 70-130° C. and the reaction time is 2-6 h.

[0013] A further improvement of the present invention is that the temperature of the self-crosslinking reaction is 200-300° C. and the time is 0.2-2 h.

[0014] A further improvement of the present invention is that the heat stabilizer is one of triphenyl phosphate, triphenyl phosphite and diphenyl phosphate.

[0015] A further improvement of the present invention is that the antioxidant auxiliary agent is one of tris(2,4-di-tert-butylphenyl) phosphite, distearic acid disulfide, didecyl disulfide and antioxidant 1010.

[0016] A further improvement of the present invention is that the melt extrusion is carried out in a twin-screw extruder, and the temperatures of zone one, zone two, zone three, zone four, zone five and the die head of the twin-screw extruder are 275°C, 280°C, 280°C, 280°C, 280°C and 275°C respectively; the screw speed of the extruder is 10-60 rpm; and the feeder speed is 1-6 rpm.

[0017] A high-impact polyethylene naphthalate composite material, the impact strength of the composite material is 80-135 kJ / m 2 , tensile strength is 70-90 MPa, Young's modulus is 1.8-2.5 GPa, and 2% mass loss temperature is >300°C.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) Significantly improve impact toughness. The present invention provides a polyacrylate elastomer with a low cross-linking structure, which can effectively improve the impact toughness of the composite material, increasing the impact strength of PEN from 2.0 kJ / m 2 Increase to 80-135kJ / m 2 , increased by 40-62.5 times, and has great prospects for industrial application.

[0019] (2) Improved processing performance. The introduction of polyacrylate elastomer can also improve the processing fluidity of PEN materials. The toughened PEN material is easier to shape during the processing, especially the injection molding and extrusion molding processes are optimized. This makes the material more adaptable to processing requirements during the production of complex-shaped products, improving production efficiency and product quality.

[0020] Furthermore, the tensile strength and modulus loss are small. The polyacrylate elastomer provided by the present invention is prepared by butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, glycidyl methacrylate and an oil-soluble initiator, has a low cross-linked structure, and its own strength is higher than that of a linear elastomer. Therefore, the composite material obtained after blending with PEN has a small loss of mechanical strength and modulus, overcoming the problem that the elastomer is a soft material and inevitably causes the loss of tensile strength and modulus after blending with PEN.

[0021] Furthermore, the heat resistance is retained. The polyacrylate elastomer provided by the present invention is first prepared by polymerization reaction and then self-crosslinking reaction, and has excellent heat resistance. After being blended with PEN, the melting point or glass transition temperature (Tg) of PEN will not be significantly reduced, which makes the toughened PEN material still suitable for high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The infrared spectrum of the low cross-linked polyacrylate elastomer provided by the present invention; Figure 2 This is a thermogravimetric curve of the high impact strength polyethylene naphthalate composite material disclosed in the present invention. DETAILED DESCRIPTION

[0023] The present invention will be described more fully below in conjunction with the embodiments. However, the present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0024] The present invention provides a method for preparing a polyethylene naphthalate (PEN) composite material with high impact strength, the steps of which are as follows: Preparation of low cross-link density polyacrylate elastomer: Put 30-50 parts of butyl acrylate, 30-50 parts of methyl methacrylate, 5-30 parts of hydroxyethyl methacrylate, 1-30 parts of glycidyl methacrylate, 0.5-1.5 parts of oil-soluble initiator and 200 parts of solvent into a four-necked flask by mass, heat to 70-130°C and react for 2-6 hours, cool to obtain a polyacrylate solution; bake the solution at 200-300°C for 0.2-2 hours to make it self-crosslinking, and obtain a low crosslinking density polyacrylate elastomer.

[0025] Furthermore, the oil-soluble initiator is one of azobisisobutyronitrile, benzoyl peroxide and di-tert-butyl peroxide. The solvent is one of toluene, xylene, mesitylene, ethyl acetate and butyl acetate or a mixture of two thereof.

[0026] Preparation of high impact strength polyethylene naphthalate composite materials: 100 parts of polyethylene naphthalate, 10-40 parts of low-crosslinked polyacrylate elastomer, 0.5-1.5 parts of heat stabilizer and 0.5-1 part of antioxidant are mixed in a mixer for 5-10 minutes by mass; then the materials are added into a twin-screw extruder for melt extrusion, and the temperatures of the first zone, the second zone, the third zone, the fourth zone, the fifth zone and the die head of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C and 275°C respectively; the screw speed of the extruder is 10-60 rpm; the speed of the feeder is 1-6 rpm, so as to obtain a polyethylene naphthalate (PEN) composite material with high impact strength.

[0027] Furthermore, the heat stabilizer is one of triphenyl phosphate, triphenyl phosphite and diphenyl phosphate; the antioxidant aid is one of tris(2,4-di-tert-butylphenyl) phosphite, distearic acid disulfide, didecyl disulfide and antioxidant 1010.

[0028] The performance evaluation method of polyethylene naphthalate composite materials is as follows: Impact strength test: The polyethylene naphthalate composite material was hot-pressed in a metal mold with a notch to obtain a test specimen. The impact strength of the specimen was tested on a cantilever beam notch impact tester (HESON, HS-JB-500B) according to GB / T3808-2002, and the test was performed three times in parallel, and the average value was recorded.

[0029] Tensile strength and Young's modulus test: The polyethylene naphthalate composite material was hot-pressed in a metal mold to obtain a test specimen. The stress-strain curve of the specimen was tested on a tensile testing machine (CMT1503) according to the GB / T 1040.1-2018 method. The experiment was conducted three times in parallel, and the average tensile strength and Young's modulus were recorded.

[0030] Thermal gravimetric test: The thermal gravimetric curve of the sample was tested on a synchronous thermal analyzer (Netzsch, Sta 449F5), and the temperature at which the mass loss was 2% was recorded.

[0031] In industry, linear elastomers are commonly used as toughening agents, which leads to a significant loss of mechanical strength and modulus, which can reach more than 40%. The elastomer in the present invention has a low cross-linked structure and its own strength is higher than that of linear elastomers. Therefore, the composite material obtained after blending with PEN has a small loss of mechanical strength and modulus. The technical solution of the present invention is described in detail below through specific embodiments: Example 1 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0032] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0033] See also Figure 1 , it can be seen that 3420 cm -1 The stretching vibration peak of hydroxyl group is 2950 cm -1 The absorption peaks of methyl and methylene are at 1720, the absorption peak of carbonyl on ester bond is at 1250 cm -1 The absorption peak of COC group generated by the reaction of hydroxyl and epoxy is 822 cm -1 The above infrared spectrum curve proves that the low cross-linked polyacrylate elastomer is successfully prepared.

[0034] See also Figure 2 It can be seen that the 2% thermal weight loss temperature of the polyethylene naphthalate composite material prepared in Example 1 is 310° C., indicating that the composite material has good thermal stability.

[0035] Example 2 Preparation of low cross-linked density polyacrylate elastomer: 30 g of butyl acrylate (BA), 50 g of methyl methacrylate (MMA), 10 g of hydroxyethyl methacrylate (HEMA), 30 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0036] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0037] Example 3 Preparation of low cross-linked density polyacrylate elastomer: 50 g of butyl acrylate (BA), 30 g of methyl methacrylate (MMA), 30 g of hydroxyethyl methacrylate (HEMA), 10 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0038] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0039] Example 4 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 0.8 g of benzoyl peroxide (BPO) and 200 g of toluene were put into a four-necked flask, heated to 120°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0040] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0041] Example 5 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.5 g of benzoyl peroxide (BPO) and 200 g of toluene were put into a four-necked flask, heated to 120°C and reacted for 2 h, and then cooled to obtain a polyacrylate solution; the solution was baked at 260°C for 1 h to cause a self-cross-linking reaction to obtain a low cross-linked polyacrylate elastomer.

[0042] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0043] Example 6 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN), 100 g of toluene and 100 g of ethyl acetate were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0044] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0045] Example 7 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN), 100 g of xylene, and 100 g of butyl acetate were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0046] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0047] Example 8 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 220°C for 1.5 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0048] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0049] Example 9 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 280°C for 0.3 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0050] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0051] Example 10 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0052] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 10 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide were mixed in a mixer for 5 min; the mixture was added into a twin-screw extruder for melt extrude, and the temperatures of the extruder zone one, zone two, zone three, zone four, zone five and the die head were 275°C, 280°C, 280°C, 280°C, 280°C, 275°C, respectively; the screw speed of the extruder was 40 rpm; the speed of the feeder was 3 rpm.

[0053] Embodiment 11 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0054] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 40 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide were mixed in a mixer for 5 min; the mixture was added into a twin-screw extruder for melt extrude, and the temperatures of the extruder zone one, zone two, zone three, zone four, zone five and the die head were 275°C, 280°C, 280°C, 280°C, 280°C, 275°C, respectively; the extruder screw speed was 40 rpm; the feeder speed was 3 rpm.

[0055] Example 12 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0056] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1.2 g of triphenyl phosphate, and 0.5 g of distearate disulfide were mixed in a mixer for 5 min; the mixture was added into a twin-screw extruder for melt extrude, and the temperatures of the extruder zone one, zone two, zone three, zone four, zone five and the die head were 275°C, 280°C, 280°C, 280°C, 280°C, 275°C, respectively; the extruder screw speed was 40 rpm; the feeder speed was 3 rpm.

[0057] Embodiment 13 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0058] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 1.0 g of antioxidant 1010 are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of the extruder zone one, zone two, zone three, zone four, zone five and the die head are 275°C, 280°C, 280°C, 280°C, 280°C, 275°C, respectively; the screw speed of the extruder is 40 rpm; the speed of the feeder is 3 rpm.

[0059] Embodiment 14 Preparation of low cross-linked density polyacrylate elastomer: 35 g of butyl acrylate (BA), 45 g of methyl methacrylate (MMA), 5 g of hydroxyethyl methacrylate (HEMA), 1 g of glycidyl methacrylate (GMA), 0.5 g of di-tert-butyl peroxide and 200 g of mesitylene were put into a four-necked flask, heated to 70°C and reacted for 6 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 200°C for 2 h to cause a self-cross-linking reaction to obtain a low cross-linked polyacrylate elastomer.

[0060] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 10 g of low-crosslinked polyacrylate elastomer, 0.5 g of diphenyl phosphate, and 1 g of tris(2,4-di-tert-butylphenyl) phosphite were mixed in a mixer for 7 min; the mixture was added into a twin-screw extruder for melt extrude, and the temperatures of the extruder zone one, zone two, zone three, zone four, zone five and die head were 275°C, 280°C, 280°C, 280°C, 280°C, 275°C, respectively; the screw speed of the extruder was 10 rpm; the speed of the feeder was 1 rpm.

[0061] Embodiment 15 Preparation of low cross-linked density polyacrylate elastomer: 45 g of butyl acrylate (BA), 35 g of methyl methacrylate (MMA), 10 g of hydroxyethyl methacrylate (HEMA), 5 g of glycidyl methacrylate (GMA), 1.5 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 130°C and reacted for 2 h, and then cooled to obtain a polyacrylate solution; the solution was baked at 300°C for 0.2 h to cause a self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0062] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 30 g of low-crosslinked polyacrylate elastomer, 1.2 g of triphenyl phosphite, and 0.7 g of didecyl disulfide were mixed in a mixer for 10 min; the mixture was added into a twin-screw extruder for melt extrude, and the temperatures of the extruder zone one, zone two, zone three, zone four, zone five and the die head were 275°C, 280°C, 280°C, 280°C, 280°C, 275°C, respectively; the extruder screw speed was 60 rpm; the feeder speed was 6 rpm.

[0063] Comparative Example 1 Preparation of low cross-linked density polyacrylate elastomer: 60 g of butyl acrylate (BA), 10 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0064] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0065] Comparative Example 2 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 50 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0066] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0067] Comparative Example 3 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 50°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0068] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0069] Comparative Example 4 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 1 h, and then cooled to obtain a polyacrylate solution; the solution was baked at 260°C for 1 h to cause a self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0070] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0071] Comparative Example 5 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 150°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0072] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0073] Comparative Example 6 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 340°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0074] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 15 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0075] Comparative Example 7 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0076] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 5 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide were mixed in a mixer for 5 min; the mixture was added into a twin-screw extruder for melt extrude, and the temperatures of the extruder zone one, zone two, zone three, zone four, zone five and the die head were 275°C, 280°C, 280°C, 280°C, 280°C, 275°C, respectively; the extruder screw speed was 40 rpm; the feeder speed was 3 rpm.

[0077] Comparative Example 8 Preparation of low cross-linked density polyacrylate elastomer: 40 g of butyl acrylate (BA), 40 g of methyl methacrylate (MMA), 20 g of hydroxyethyl methacrylate (HEMA), 20 g of glycidyl methacrylate (GMA), 1.0 g of azobisisobutyronitrile (AIBN) and 200 g of toluene were put into a four-necked flask, heated to 100°C and reacted for 4 h. After cooling, a polyacrylate solution was obtained; the solution was baked at 260°C for 1 h to cause self-crosslinking reaction to obtain a low cross-linked polyacrylate elastomer.

[0078] Preparation of high impact strength polyethylene naphthalate composite material: 100 g of polyethylene naphthalate, 50 g of low-crosslinked polyacrylate elastomer, 1 g of triphenyl phosphite, and 0.5 g of distearate disulfide are mixed in a mixer for 5 min; the mixture is added into a twin-screw extruder for melt extrude, and the temperatures of zones 1, 2, 3, 4, 5 and the die of the extruder are 275°C, 280°C, 280°C, 280°C, 280°C, and 275°C, respectively; the screw speed of the extruder is 40 rpm; and the speed of the feeder is 3 rpm.

[0079] The raw materials and conditions in Examples 1-13 and Comparative Examples 1-8 of the present invention are shown in Table 1, and the performance comparison is shown in Table 2.

[0080] Table 1 Synthetic data of examples and comparative examples

[0081] Table 2 Comparison of the properties of PEN resins obtained in Examples and Comparative Examples

[0082] According to Examples 1-13 and Comparative Examples 1-8, the synthetic polyacrylic acid elastomer monomers BA and GMA in Comparative Examples 1 and 2 exceed the dosage ratio range of the present invention, resulting in an increase in the glass transition temperature of the synthesized polyacrylate resin, which cannot reflect the elastomer characteristics and leads to poor toughening effect. In Comparative Example 3, the polycondensation reaction temperature is lower than the reaction temperature range of the present invention. The polycondensation temperature is too low, resulting in a slow polycondensation reaction rate, forming an oligomer solution, which cannot play a toughening role. The polycondensation reaction time of Comparative Example 4 is too short, which also leads to a low molecular weight of polyacrylate, forming an oligomer solution, which cannot play a toughening role. The post-crosslinking temperature of the polyacrylate solution in Comparative Examples 5 and 6 exceeds the temperature range of the present invention. Comparative Example 5 is too low, resulting in an inability to form a cross-linked structure; the cross-linking temperature of Comparative Example 6 is too high, resulting in a high degree of cross-linking, and cannot be melt processed. In Comparative Examples 7 and 8, the content of the low-crosslinked polyacrylate elastomer melt-blended with PEN exceeds the dosage range of the present invention. In Comparative Example 7, the amount of elastomer is too small to promote the plastic deformation of the matrix; in Comparative Example 8, the amount of elastomer is too large to form particles with larger particle size in the resin, resulting in poor toughening effect.

[0083] As shown in Table 2, the high impact resistant polyethylene naphthalate composite material prepared by the present invention has excellent impact performance of 80-135 kJ / m 2 , which can reach 40-62.5 times that of pure PEN resin (pure PEN resin is 2.0 kJ / m 2 ). At the same time, the PEN composite material also has good mechanical properties, with a tensile strength of 70-90 MPa and a Young's modulus of 1.8-2.5 GPa, which meets the performance requirements of engineering plastics in most application scenarios. In addition, the composite material also has good thermal stability, with a 2% mass loss temperature greater than 300°C, which further broadens its application scenarios.

[0084] The PEN composite material prepared by the method of the present invention avoids the defect of poor impact performance of pure PEN resin, significantly improves the impact toughness while maintaining good mechanical properties. In addition, it has excellent thermal stability and processing performance, and has great application value in the field of engineering plastics.

[0085] In the present invention, polyacrylate elastomer with low cross-linking density is dispersed into PEN resin to form a phase morphology with low matrix ligament thickness, which can effectively increase the ductility of PEN, so that it can show better energy absorption and deformation ability under impact, thereby avoiding brittle fracture. The composite material of the present invention avoids the defect of poor impact performance of pure PEN resin, and significantly improves impact toughness while maintaining good mechanical properties. In addition, it has excellent thermal stability and processing performance, excellent comprehensive performance, simple preparation process, easy to obtain raw materials, and broad prospects for industrial application.

[0086] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0087] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a polyethylene naphthalate composite material with high impact strength, characterized in that: The following steps are involved: 100 parts of polyethylene naphthalate, 10-40 parts of polyacrylate elastomer, 0.5-1.5 parts of heat stabilizer and 0.5-1 parts of antioxidant are mixed uniformly by mass, melt-extruded and obtained to obtain polyethylene naphthalate composite material with high impact strength.

2. The method for preparing the polyethylene naphthalate composite material with high impact strength according to claim 1, characterized in that: The polyacrylate elastomer is prepared by the following process: by weight, 30-50 parts of butyl acrylate, 30-50 parts of methyl methacrylate, 5-30 parts of hydroxyethyl methacrylate, 1-30 parts of glycidyl methacrylate, 0.5-1.5 parts of an oil-soluble initiator and 200 parts of a solvent are polymerized to obtain a polyacrylate solution; and the polyacrylate solution is subjected to a self-crosslinking reaction under heating to obtain a polyacrylate elastomer.

3. The method for preparing the polyethylene naphthalate composite material with high impact strength according to claim 2, characterized in that: The oil-soluble initiator is one of azobisisobutyronitrile, benzoyl peroxide and di-tert-butyl peroxide.

4. The method for preparing the polyethylene naphthalate composite material with high impact strength according to claim 2, characterized in that: The solvent is one or a mixture of two of toluene, xylene, mesitylene, ethyl acetate and butyl acetate.

5. The method for preparing the polyethylene naphthalate composite material with high impact strength according to claim 2, characterized in that: The polymerization temperature is 70-130°C and the time is 2-6 h.

6. The method for preparing the polyethylene naphthalate composite material with high impact strength according to claim 2, characterized in that: The temperature of the self-crosslinking reaction is 200-300°C and the time is 0.2-2 h.

7. The method for preparing the polyethylene naphthalate composite material with high impact strength according to claim 1, characterized in that: The heat stabilizer is one of triphenyl phosphate, triphenyl phosphite and diphenyl phosphate.

8. The method for preparing the polyethylene naphthalate composite material with high impact strength according to claim 1, characterized in that: The antioxidant auxiliary agent is one of tris(2,4-di-tert-butylphenyl)phosphite, distearic acid disulfide, didecyl disulfide and antioxidant 1010.

9. The method for preparing the polyethylene naphthalate composite material with high impact strength according to claim 1, characterized in that: The melt extrusion is carried out in a twin-screw extruder. The temperatures of zone 1, zone 2, zone 3, zone 4, zone 5 and the die head of the twin-screw extruder are 275°C, 280°C, 280°C, 280°C, 280°C and 275°C respectively; the screw speed of the extruder is 10-60 rpm; the feeder speed is 1-6 rpm.

10. A polyethylene naphthalate composite material with high impact strength prepared by the method according to any one of claims 1 to 9, characterized in that: The impact strength of the composite material is 80-135 kJ / m 2 , tensile strength is 70-90 MPa, Young's modulus is 1.8-2.5 GPa, and 2% mass loss temperature is >300°C.

Citation Information

Patent Citations

  • High-impact polyethylene terephthalate (PET) composite material and preparation method thereof

    CN102382432A

  • Polyethylene naphthalate resin composition and preparation method thereof

    CN103396658A

  • A toughened modified transparent PET sheet composite material and its preparation method

    CN105482387B

  • Co-fixing polyethylene terephthalate in high tenacity and preparation method

    CN1279115C

  • Active group containing polyacrylate flexibilizer, preparation method thereof and epoxy resin adhesive modified by same

    CN101993670A

Cited By

  • Modified polycarbonate master batch, composite polycarbonate material as well as preparation method and application of modified polycarbonate master batch and composite polycarbonate material

    CN121699364A